Stress and its associated factors among primary school teachers at Kinta Valley - a cross sectional study / Elliani Mohamed Saaid - Mohamed Saaid, Elliani (2017)
Background: Teacher is a profession known to have exposure to a great amount of stress. Factors that have association with stress vary between research studies. The government of Malaysia had introduced the new Malaysian Education Blueprint (2013-2015) which is aimed to increase the performance of the Malaysian education sector. These new challenges to the teachers may serve as a new factor to occupational stress. Literatures have shown that teachers who experienced great level of stress will have negative impact to their relationship with students. Objectives: This study is aimed to determine the prevalence of stress among primary school teachers at Kinta Valley, as well as to study the sociodemographic factors and job characteristics that contributed to stress. We determined the subjects' depression and anxiety status and their association with stress. Methodology: This is a cross-sectional study involving 104 primary school teachers. The samples were recruited through cluster random sampling. Study instruments used were sociodemographic from, Depression, Anxiety and Stress 21-item scale (DASS 21) and Teacher Concern Inventory by Fimian (1988). Descriptive analysis was performed, followed by multiple logistic regression analysis. Results: The prevalence of stress among the primary school teachers was found to be 14.4%. Among the sociodemographic factors that were studied, none of those were found to have association with stress. Nonetheless, type of teacher (administrators, classroom or subject teachers) was found to have statistically significant association with stress (p=0.046). 18.3% of the respondents were depressed, while 47.1 % respondents were screened as anxious. However, it is important to note that DASS2 l is not a diagnostic tool. Both depression and anxiety had significant association with stress (both p values=0.00). Following the multiple logistic regression analysis, only depression remained to have statistical significant association with stress (OR=56.32, 95% CI = 10.49 - 302.36). Conclusion: Stress among primary school teachers is prevalent. Among those who had depressive symptoms, they were highly likely to experience stress with odds 56 times higher. Nevertheless, the confidence interval is wide, owing to the small sample size of our study. This study implicates that teachers do experience stress and they are at risk to develop depression due to this. The policy maker should take appropriate measures to overcome this ongoing issue. However, we suggest that future research should include more teachers, more different type of schools and uses diagnostic instruments so as to make the study more impactful. Additionally, protective factors to stress should be studied as well. Limitation of time and resources has served as a major factor to the limitations of our study.